Fifteen years of Belgian experience with external quality assessment of semen analysis. (13th July 2016) - Punjabi, U.; Wyns, C.; Mahmoud, A.; Vernelen, K.; China, B.; Verheyen, G.
Summary: Semen analysis is difficult to standardize, quality control and quality assurance are necessary to ensure that results are accurate and precise. This Belgian EQA survey over a 15‐year period, involving 121 laboratories, attempted to reduce interlaboratory variability and at the same time, encouraged participating laboratories to implement correct techniques as advised by the WHO. Over the total period, the median coefficient of variation (CV) for sperm count, irrespective of the method used was 19.2%, while using improved Neubauer chamber resulted in a significantly ( p  < 0.001) lower median CV (14.4%). The overall median CV for rapid progressive motility was high (37.1%), but progressive motility (15.1%) and total motility (13.8%) were acceptable. Sperm morphology revealed a large variability in 79.4% irrespective of the staining procedures or evaluation criteria used. Participation in the Belgian EQA is on voluntary basis. Both, participation and implementation of the correct techniques should be made mandatory for accreditation and benefit of patient treatment. The existing Belgian EQA program should now be harmonized with other existing EQA schemes in Europe.